2018
DOI: 10.22319/rmcp.v9i2.4232
|View full text |Cite
|
Sign up to set email alerts
|

Detección molecular y serológica del virus de la leucosis bovina en una población de vacas Holstein, de Colombia

Abstract: La leucosis bovina enzoótica (LBE) es una enfermedad maligna, sistémica, de alta morbilidad (70 %) y baja mortalidad, ocasionada por la infección con el virus de la leucosis bovina (BLV). La LBE afecta principalmente los bovinos de leche, disminuyendo la producción de leche de 2.5 a 5 % respecto al hato; además, causa inmunosupresión, permitiendo que otros patógenos afecten la producción y reproducción de los animales. El objetivo fue determinar la presencia o ausencia del BLV a través de dos metodologías de d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Molecular epidemiology studies of BLV worldwide an in this case in Colombia, makes it possible to identify circulating strains in specific regions to propose and build public policies aimed to control and, in the future, eradicate this virus which has been seen to produce problems not only in cattle but also has been reported as a possible risk factor involved in humans pathologies [32][33][34][35]. In the other hand, variability of genotypes as well as results of structural and functional properties of its envelope proteins [36] provide useful information for research focused on vaccines production with specific strains, that in the case of Colombia, will be appropriate to include conserved epitopes shared between genotypes 1, 6 and 3 according to the results obtained in this study and previously reported [31]. In addition, phylogenetic studies are important to understand the geographical distribution of the virus and thus, identify conserved and hypervariable regions including specific mutations that could be related with different levels of virulence or pathogenicity [6,[37][38][39][40][41].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Molecular epidemiology studies of BLV worldwide an in this case in Colombia, makes it possible to identify circulating strains in specific regions to propose and build public policies aimed to control and, in the future, eradicate this virus which has been seen to produce problems not only in cattle but also has been reported as a possible risk factor involved in humans pathologies [32][33][34][35]. In the other hand, variability of genotypes as well as results of structural and functional properties of its envelope proteins [36] provide useful information for research focused on vaccines production with specific strains, that in the case of Colombia, will be appropriate to include conserved epitopes shared between genotypes 1, 6 and 3 according to the results obtained in this study and previously reported [31]. In addition, phylogenetic studies are important to understand the geographical distribution of the virus and thus, identify conserved and hypervariable regions including specific mutations that could be related with different levels of virulence or pathogenicity [6,[37][38][39][40][41].…”
Section: Discussionsupporting
confidence: 57%
“…However, topology of some trees shows different clusters in the same genotype, leading to the question if the amplification of the 444 bp segment of env region could efficiently identify all the current genotypes or instead, it mimics the presence of other circulating genotypes. Now, considering the current situation of BLV in Colombia, even if it was determined the seroprevalence earlier [1], there are few studies [31] in which the molecular epidemiology of the virus has been determined. The aim of this study was to identify the circulating genotype of BLV along the country in order to deep in the knowledge of the current situation of BLV and to reveal the possibility of masked genotypes, unable to identify with the primers suggested by OIE.…”
Section: Introductionmentioning
confidence: 99%
“…In Colombia, percentages of antibodies against BLV have been determined in 13.5% of cattle from Toca (Boyacá) using Göttingen hematological keys and ELISA ( Pulido-Medellín et al , 2017 ), in 21.8% of individuals from the department of Santander ( Vargas-Niño et al , 2018 ), in 79.17%, 53.74%, and 46.67% in the Oriente, Norte, and Valle de Aburrá subregions (Antioquia), respectively ( Úsuga-Monroy et al , 2018a ), 31.1% in Sotaquirá (Boyacá) ( Bulla-Castañeda et al , 2021 ), 14.64% in Puerto Boyacá ( Naranjo et al , 2022 ), and 31.1% of the animals sampled in Paipa (Boyacá) ( Jiménez Sánchez et al , 2022 ). Variations occur due to the number of animals sampled, management practices, and production intensification, as well as the geographical location of the farms since it has been reported that there is a greater tendency to seropositivity to the disease in farms with temperate climate and higher altitude, that is mainly associated with sanitary and management practices such as re-use of needles, rectal palpation gloves, natural matting, among others ( Vásconez-Hernández et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This retrovirus is closely related to the types of human lymphotropic T-cell leukaemia virus (HTLV-1 and -2) [3]. BLV integrates its genome in target bovine cells, so that all infected animals are persistently infected and become carriers of the virus during the course of their lives, thereby having a negative impact on the animals' immune system and, consequently, induces losses in milk production, poorer yield regarding weight and induced abortions in the animals [1,4,5].…”
Section: Introductionmentioning
confidence: 99%